Envelope-associated folded chromosomes for Escherichia coli: variations under different physiological conditions. - Korch, C (1976)
The folded chromosome of Escherichia coli has been investigated under various lysis and physiological conditions. A new gradient system was devised that allows excellent separation between unlysed cells and envelope-associated and envelope-free chromosomes. Isotope incorporation experiments showed that the fraction often called "membrane-bound nucleoids" contains cell wall in addition to nucleic acids, membranes, and proteins. The amount of lysozyme added and the lysozyme digestion time were found to be important when comparing the rate of sedimentation of envelope-associated chromosomes obtained under various physiological conditions. Amino acid-starved cells were found to be much harder to lyse with lysozyme than exponentially grown cells, The difference in sedimentation coefficient of envelope-associated chromosomes described earlier (Ryder and Smith, 1974) was not detected when the latter two types of cells had been given equivalent, but not identical, lysozyme treatment such that detergent-mediated lysis proceeded at the same rate. Analysis of pulse- and uniformly labeled chromosomes from amino acid-starved cultures revealed no preferential labeling of either envelope-associated or -released nucleoids. Nor was there a difference in sedimentation coefficient between uniform and pulse-labeled envelope-associated nucleoids. These results are in disagreement with the models for chromosome replication of Worcel and Burgi (1974) and Ryder and Smith (1974), respectively. Growing cells on carbon sources poorer than glucose demonstrated that the replicating chromosomes sediment faster than the bulk of envelope-associated nucleoids. The slower the growth rate, the greater this difference became. An alternative hypothesis regarding chromosome replication and its association with the cell envelope is presented.